2019
DOI: 10.30534/ijatcse/2019/2681.62019
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Stability Measurement of Linear Voltage Regulator in the Closed-loop Condition

Abstract: Few factors may contribute to the stability of a linear voltage regulator (LVR). Among them is the value of the capacitor connected to the output terminal of the LVR, with the primary factor being the parasitic element of the capacitor, namely, equivalent series resistance. The LVR operation is based on the closed-loop system mechanism. LVR stability can be analyzed through two types of responses, namely, transient and frequency. This research focuses on the frequency response of the closed-loop system in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Generally, each sinusoidal signal is capable of testing two frequency components at a time. Therefore, at least three different types of sinusoidal signals are needed for six frequency components or coefficients, as in (11). However, four sinusoidal signals are used to improve the accuracy of the estimated model.…”
Section: Model Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, each sinusoidal signal is capable of testing two frequency components at a time. Therefore, at least three different types of sinusoidal signals are needed for six frequency components or coefficients, as in (11). However, four sinusoidal signals are used to improve the accuracy of the estimated model.…”
Section: Model Simulationmentioning
confidence: 99%
“…Firstly, the number of sinusoidal signals depends on the number of frequency components or the number of coefficients in the A v model. In this study, we have six frequency components, as shown in (11); thus, at least three sinusoidal signals are required. However, four sinusoidal signals are used to increase the level of accuracy.…”
Section: A Validation Of Input Signalmentioning
confidence: 99%
See 1 more Smart Citation